Students’ Perceptions of Sustainable Tourism Trends in Indonesia - Prasetyo, Andreas; Hidayah, Atika Nur; Kurniasari, Kenyo Kharisma (International Journal of Sustainable Competitiveness on Tourism, 2026)
This study aims to analyze students’ perceptions of sustainable tourism development in Indonesia, focusing on the economic, socio-cultural, and environmental dimensions. Using a quantitative survey method, data were collected from 128 students across several universities in Indonesia through online and offline questionnaires. Descriptive statistical analysis was employed to identify perception patterns and awareness levels toward sustainable tourism principles. The results indicate that students generally have a positive perception of sustainable tourism. The economic aspect gained the highest mean score (2.10), reflecting optimism toward tourism’s role in improving livelihoods and supporting regional economic growth. The socio-cultural dimension (mean 2.24) showed positive attitudes accompanied by awareness of social and cultural risks. The environmental dimension (mean 2.20) revealed that students appreciate tourism’s potential to foster environmental awareness while acknowledging possible ecological degradation. These findings suggest that Indonesian students possess a balanced and critical understanding of sustainability principles and highlight the importance of integrating sustainability education into tourism curricula to prepare responsible future professionals.